The Attitude of Middle school headmasters to wards the Practice of Sport and physical education - mili, faiza (sports creativity, 2025)
The study aims to know the attitude of middle schools headmasters towards the practice of sport and the physical education and in order to achieve the goals of the study, the researcher used the descriptive analytical method and designed a questionnaire to collect the necessary data and information The study was conducted on a sample consisting of eleven headmasters at the level of Algiers. The results showed that most school headmasters at the positive attitude towards sport and the physical education as being a basic subject in the educational system.